Evaluation of the effect of the Zielony Busz fertilizer on selected phytopathogenic fungi growth in vitro - Jamiołkowska, Barbara; Skwaryło-Bednarz, Barbara; Kursa, Weronika (Polish Journal of Agronomy, 2022)
The aim of the research was the laboratory evaluation of the fungistatic effect of the Zielony Busz (ZB) organic-mineral fertiliser on the linear growth of polyphagic phytopathogenic fungi Alternaria alternata, Colletotrichum coccodes, Fusarium avenaceum, Fusarium equiseti and Fusarium oxysporum. The preparation was applied to the medium (PDA potato-glucose agar) in concentrations of 2% and 5%, compared to 0.05% azox- ystrobin (relative control) and pure PDA medium (absolute con- trol). The strongest antifungal effect of the Zielony Busz fertilizer was found at the 5% concentration in reference to A. alternata (inhibition of colony growth at the level of 50–52% compared to the absolute control; 20–41.7% compared to azoxystrobin) and C. coccodes (18.2–53.3% growth inhibition compared to abso- lute control). Weaker inhibitory effect of 5% concentration of the fertilizer was noted against F. avenaceum (10.5% inhibition of colony growth compared to absolute control) and F. oxysporum (20% inhibition compared to absolute control), but only at the beginning of the experiment. The Zielony Busz fertilizer at a con- centration of 2% caused the surface growth of all tested fungi, especially F. equiseti. The best effects of the fungistatic effect of the fertilizer were obtained in the first days of the experiment (4th day) with a 5% concentration of the product in the substrate. With time, the antifungal activity of fertilizer decreased significantly.